Improved poultry variety for income and nutritional security in semi-arid areas of Telangana - Pankaj, Prabhat Kumar; Nirmala, G; Shankar, K Ravi; Reddy, B Sanjeev; Chary, G Ravindra (Indian Farming, 2019)
Development of organized poultry has marked the contribution of backyard or household poultry in rural areas of Telangana where rural poultry constitutes about 27% of the total poultry population. In order to improve nutrient availability of poor households in rural areas of Vikarabad district, Telangana, low input technology backyard poultry farming using Srinidhi breed was introduced under Farmer FIRST Programme for supplementing the earnings of poor farmers and landless labourers. The nutritional status pre-and post-intervention was assessed and as per the production and reproduction performance data obtained on Srinidhi poultry, their role in reducing the nutritional deficiency in the area was demonstrated to the farmers. The study revealed significant higher production performances of Srinidhi variety over the indigenous poultry birds and has a better support system to livelihood and nutritional security under backyard poultry production in the dryland region.